Out-of-school adolescents in South West Nigeria: a concern to stakeholders (2012)
The growing number of children that is seen in the streets of south-western part of Nigeria while their counterparts are in schools receiving formal education has become a concern to stakeholders in education. It is now a common thing to see school age children involved in menial jobs like bus conducting, street hawking, house helping and even begging for alms in the streets while their peers are in regular schools. In order to curb this trend, the study therefore investigated the phenomenon of out-of-school children in South West, Nigeria. The study was guided by three research hypotheses. It is a descriptive survey research in which 1200 out-of-school adolescents were randomly selected from the six states that comprises the South-West region of Nigeria. The study discovered that the six predictor variables (lack of finance, single parentage, separated home, peer pressure, truancy and others) contributed significantly to the criterion variable (out-of- school children). The study also revealed that gender is related to the choice of career of out-of-school children. The study also discovered that gender has a significant contribution to out-of-school children rate in Nigeria. It was therefore recommended that relevant stakeholders should assist out-of-school children to return to school. Also, children who are not interested in schooling should be aided to learn one trade or the other.